Exocyclic DNA adducts as oxidative stress markers in colon carcinogenesis: potential role of lipid peroxidation, dietary fat and antioxidants - Bartsch, Helmut; Nair, Jagadeesan; Owen, Robert (Biological chemistry, 2005)
Abstract Molecular pathways to colorectal cancer involve multiple - genetic changes, whereby extensive oxyradical - damage causes mutations in cancerrelated genes - and leads to a cycle of cell death and regeneration. Besides - direct oxidative DNAdamage, reactive oxygen - and nitrogen species can induce etheno ()DNA - adducts mainly via trans-4-hydroxy-2-nonenal, generated - as the major aldehyde by lipid peroxidation (LPO) - of ω-6 PUFAs. Patients with familial adenomatous - polyposis (FAP) develop multiple colorectal adenomas. - In affected tissues increased LPO could be triggered - due to increased arachidonic acid metabolism - as a result of elevated cyclooxygenases. Our studies - demonstrated an increased DNA adduct level in affected - colon epithelia of FAP patients. DNA adducts - are promutagenic and can cause genomic instability - that drives colorectal adenoma to malignancy. We - have further investigated the potential chemopreventive - properties of olive oil and its polyphenolic components. - Mediterranean diet, of which olive oil is a major - fatty acid source, has protective effects against human - breast and colorectal cancers. Olive oil extracts - and the newly identified lignan fractions showed high - antioxidant capacity in vitro. As DNA adducts are - biomarkers for oxidative stress and LPO induced DNA - damage, they can verify the efficacy of newly identified - antioxidants, e.g. from olive oil, as chemopreventive - agents against colon carcinogenesis.